Drag variations, tidal asymmetry and tidal range changes in a mangrove creek system. Issue 9 (5th May 2021) - Horstman, Erik M.; Bryan, Karin R.; Mullarney, Julia C.
Abstract: Aboveground root structures enhance drag on tidal currents in intertidal mangrove forests, whereas the creeks dissecting such forests provide low‐resistance conduits for tidal flows. Here, observations from an established mangrove forest in the Whitianga Estuary, Aotearoa New Zealand, are used to investigate the variability of the drag experienced by tidal flows in a mangrove creek system and subsequent effects on tidal asymmetries and ranges. Tidal flow speed maxima in the creek occurred at overbank water levels during the sheet flow stage on rising tides, but at water levels below the creek bank (the creek flow stage) on falling tides. Inferred bulk drag coefficients for the creek were greater during the sheet flow than the creek flow stage, and were linearly correlated with the bulk drag coefficients at stations in the adjacent forest. Although falling tides, associated with larger bulk drag coefficients, had an increasingly longer duration than rising tides towards the back of the forest, we observed ebb‐dominant flow speed asymmetry that declined inland in the creek. Conversely, flow speeds within the forest were consistently flood‐dominant, in accordance with smaller bulk drag coefficients during rising tides. Along the full length of the mangrove system, high‐water levels were lowered by up to 12 cm/km within the creek and 36 cm/km within the mangrove forest. Creek bed roughness associated with bulk drag coefficients observed in deeper parts of the creek was much greater than the hydraulic roughness of the sediment. For accurate simulations of landscape‐scale feedbacks between the creek and mangrove forest, incorporating both direct and indirect contributions of the vegetated forest platform to creek bed roughness is essential. These findings show that the interaction between creek flow and sheet flow in a mangrove creek system is a key driver of tidal asymmetries as well as the attenuation of high‐water conditions. Abstract : Drag coefficients in a mangrove creek system are found to vary with vegetation density and tidal stage. These variations differentially change tidal wave speeds during rising and falling tides, causing tidal asymmetries. Flow speeds and water level gradients along the creek correlate with the vegetation on the banks. Interactions between creek and sheet flows in the mangrove system affect the inferred drag coefficients and are therefore imperative for understanding the system's tidal asymmetries and ranges.